PENGARUH PEMBELAJARAN QUANTUM TEACHING TERHADAP PENINGKATAN HASIL BELAJAR SISWA MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM KELAS VIII MTS AL-FAAIZUN WATANG PALAKKA - Rahman, Abd.; Wardana, Wardana (Institut Agama Islam Negeri (IAIN) Bone, 2021)
AbstractPreliminary study conducted by researchers at MTs Al-Faaizun Watang Palakka showed that in the learning process, teachers still use teacher-centered learning approach, so that teachers can not get closer to students with lesson experience and students are still lacking in critical thinking skills, active, creative and construct its knowledge, where the ability can have a positive impact in improving learning outcomes. In this study used learning Quantum Teaching and Mind Mapping method.With the main problem is whether there is influence of learning Quantum Teaching to improve student learning outcomes. This issue is seen with paedagogical approach and discussed with quantitative methods.The purpose of this research are: (1) to know the application of Quantum Teaching learning with Mind Mapping method on learning History of Islamic Culture of VIII students of MTs Al-Faaizun Watang Palakka, (2) to know the influence of Quantum Teaching learning with Mind Mapping method on learning History of Islamic Culture grade VIII student MTs Al-Faaizun Watang Palakka.The population in this research is all students of class VIII MTs Al-Faaizun Watang Palakka Lesson Year 2016/2017 which amounted to 162 students. Sampling was done by using cluster random sampling and obtained class VIII.A as control class and class VIII.C as experiment class. Methods of data collection using test methods and documents.